Substansi Budaya dalam Kebijakan Tata Ruang di Bali - Gusti Ayu Made Suartika (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
This article analyses essential elements of Balinese culture, which are formulative of land use planning for Bali. Using ethnographic and hermeneutic methodologies and a cultural matrix derived from E.T. Hall (1973), strategic territorialities are defined and correlated to nine dimensions of culture. The study is contextualised by the ongoing debate over the challenges Bali faces in conserving its cultural heritage while achieving its development objectives. The results emerge from Fundamental Research Scheme funded by the Indonesian Department for Education.